New Targets in Heart Failure Drug Therapy - Correale, Michele; Tricarico, Lucia; Fortunato, Martino; Mazzeo, Pietro; Nodari, Savina; Di Biase, Matteo; Brunetti, Natale Daniele (Frontiers in Cardiovascular Medicine, 2021)
Despite recent advances in chronic heart failure management (either pharmacological or non-), prognosis of acute HF patients remains poor, with significant HF rehospitalization or death rates in the six months after discharge. This poor prognosis emphasizes the need for developing novel pathways for testing new HF drugs, beyond neurohumoral and hemodynamic modulation approach. The development of new drugs for HF therapy must thus necessarily focuse on a novel approaches such as direct effect on cardiomyocytes, coronary microcirculation, and myocardial interstitium. This review summarizes principal evidence on new possible pharmacological targets for the treatment of HF patients, mainly focusing on microcirculation, cardiomyocyte and anti-inflammatory therapy.